2021
DOI: 10.1007/s10792-021-01799-w
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intravitreal ziv-aflibercept in patients with macular edema following retinal vein occlusion in Korle-Bu Teaching Hospital, Ghana: a retrospective case series

Abstract: Aim To evaluate the efficacy of ziv-aflibercept in Ghanaian patients with macular edema (ME) secondary to retinal vein occlusion (RVO). Methodology In this retrospective study, the medical records of patients with ME secondary to RVO who had been treated with intravitreal ziv-aflibercept (IVZ) (1.25 mg/0.05 ml), as part of routine clinical practice, on pro re nata basis with a minimum follow-up of 6 months were retrieved and analyzed. The main outcome mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The anti-VEGF drugs have been widely used in ocular diseases such as exudative age-related macular degeneration, diabetic macular edema, choroidal neovascularization, and RVO-ME, and have shown good safety and efficacy. Previous retrospective and prospective studies have shown that the anti-VEGF treatment for RVO-ME in real-word has achieved significant retinal structure improvement and visual function recovery ( 5 , 17 , 29 , 33 , 37 , 38 ). The patients included in this study are divided into the mAb group (ranibizumab injection) and the Fc group (injection of conbercept or aflibercept) according to their mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The anti-VEGF drugs have been widely used in ocular diseases such as exudative age-related macular degeneration, diabetic macular edema, choroidal neovascularization, and RVO-ME, and have shown good safety and efficacy. Previous retrospective and prospective studies have shown that the anti-VEGF treatment for RVO-ME in real-word has achieved significant retinal structure improvement and visual function recovery ( 5 , 17 , 29 , 33 , 37 , 38 ). The patients included in this study are divided into the mAb group (ranibizumab injection) and the Fc group (injection of conbercept or aflibercept) according to their mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, age and disease duration are baseline factors that can affect visual function following anti-VEGF treatment ( 16 , 31 ). The eyes of ME secondary to BRVO are showing a better visual prognosis compared with CRVO ( 32 , 33 ). In this study, younger patients with a shorter disease duration are associated with better visual outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Ziv-aflibercept has an identical molecular structure and mechanism of action as aflibercept, which makes it potentially available for ophthalmic use at a much lower cost. Although previous studies have demonstrated that both ziv-aflibercept and bevacizumab appear safe and effective for the treatment of ME secondary to CRVO, [5][6][7][10][11][12][13][14] a prospective comparison between these drugs has never been reported. Therefore, this study aimed to compare the efficacy of intravitreal ziv-aflibercept (IVZ) and intravitreal bevacizumab (IVB) treatment in patients with ME secondary to CRVO over a 6-month period.…”
Section: Introductionmentioning
confidence: 99%